A bounded actor–critic reinforcement learning algorithm applied to airline revenue management. (June 2019) - Lawhead, Ryan J.; Gosavi, Abhijit
Abstract: Reinforcement Learning (RL) is an artificial intelligence technique used to solve Markov and semi-Markov decision processes. Actor critics form a major class of RL algorithms that suffer from a critical deficiency, which is that the values of the so-called actor in these algorithms can become very large causing computer overflow. In practice, hence, one has to artificially constrain these values, via a projection, and at times further use temperature-reduction tuning parameters in the popular Boltzmann action-selection schemes to make the algorithm deliver acceptable results. This artificial bounding and temperature reduction, however, do not allow for full exploration of the state space, which often leads to sub-optimal solutions on large-scale problems. We propose a new actor–critic algorithm in which (i) the actor's values remain bounded without any projection and (ii) no temperature-reduction tuning parameter is needed. The algorithm also represents a significant improvement over a recent version in the literature, where although the values remain bounded they usually become very large in magnitude, necessitating the use of a temperature-reduction parameter. Our new algorithm is tested on an important problem in an area of management science known as airline revenue management, where the state-space is very large. The algorithm delivers encouraging computational behavior, outperforming a well-known industrial heuristic called EMSR-b on industrial data.